The Effects of Hobby Activities on Self-esteem of Persons with Disabilities : Focusing on the Mediating Effect of Self-efficacy - Young-soo, Kim; Hong-jik, Lee (Korean Journal of Social Quality, 2025)
This study aims to verify how hobby activities affect self-esteem of persons with disabilities, mediated by self-efficacy. Using the data from The 8th Wave of the 2nd Panel Survey of Employment for the Disabled, this study conducted analysis of mediating effects and Sobel test on a sample of 295 registered persons with disabilities. The results revealed that hobby activities positively influenced self-efficacy, which in turn had a positive effect on self-esteem. Furthermore, the mediating effect of self-efficacy on the relationship between hobby activities and self-esteem was confirmed to be statistically significant. These findings suggest that hobby activities could contribute to enhancing the quality of life for persons with disabilities. Accordingly, this study proposes a re-examination of the value of hobby activities within disability welfare practices, and recommends the active implementation of programs, particularly those that minimize the pressure of failure. KCI Citation Count: 0